STERILE ENDOPHTHALMITIS FOLLOWING CATARACT SURGERY IN THE LEFT EYE: A RARE CASE REPORT OF TOXIC ANTERIOR SEGMENT SYNDROME (TASS) - Costrila, Caroline; Faozan (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Toxic anterior segment syndrome (TASS) is a complicated condition following eye surgery. TASS is sterile and can occur due to non-infectious toxic substances with various etiologies. A 55-year-old man diagnosed with oculi sinistra toxic anterior segment syndrome, oculi dextra astigmatism composite myopia and oculi dextra et sinistra presbyopia with pseudophakia that occurred after cataract surgery with phacoemulsion technique and administration of ciprofloxacin eye drops. Ciprofloxacin, an antibiotic, can cause ocular toxicity by depositing on the cornea surface. The precipitation is closely related to the PH of the tear film